Intrinsic and extrinsic drivers of autotrophic nitrogen cycling in stream ecosystems: Results from a translocation experiment. (12th October 2014) - Peipoch, Marc; Gacia, Esperança; Pastor, Ada; Ribot, Miquel; Riera, Joan Ll.; Sabater, Francesc; Martí, Eugènia
Abstract : We investigated the intrinsic (i.e., metabolic character of autotrophs) and extrinsic (i.e., nutrients and light availability) controls on the variation in autotrophic nitrogen (N) cycling in stream ecosystems based on 15 N isotopic incorporation into five autotrophic components (biofilm, filamentous algae, bryophytes, and submerged and emergent macrophytes) differing in structural complexity and metabolic character. Autotrophs from a stream site with depleted 15 N signatures and relatively low concentrations of dissolved inorganic N (DIN) were translocated to three reaches downstream of the same stream with higher 15 N–DIN signatures and DIN concentrations and different light availability. After the translocation, autotrophs showed an asymptotical increase in their 15 N signatures, achieving isotopic equilibrium with the stream water, from which we calculated N uptake and turnover rates for each autotrophic compartment at the three reaches. Uptake rates were highest when both DIN and light availability were also highest. Differences in DIN uptake rates were greater across reaches than among autotrophs, suggesting that autotrophic DIN uptake at both organism and community level is principally controlled by extrinsic factors (e.g., DIN concentration and light incidence). In contrast, variation in N turnover rates was larger among the different autotrophs than among the study reaches, suggesting a stronger control by intrinsic rather than extrinsic factors.